2021
DOI: 10.1093/nar/gkab1035
|View full text |Cite
|
Sign up to set email alerts
|

lncRNAfunc: a knowledgebase of lncRNA function in human cancer

Abstract: The long non-coding RNAs associating with other molecules can coordinate several physiological processes and their dysfunction can impact diverse human diseases. To date, systematic and intensive annotations on diverse interaction regulations of lncRNAs in human cancer were not available. Here, we built lncRNAfunc, a knowledgebase of lncRNA function in human cancer at https://ccsm.uth.edu/lncRNAfunc, aiming to provide a resource and reference for providing therapeutically targetable lncRNAs and intensive inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 70 publications
0
59
0
Order By: Relevance
“…Many of these lncRNAs are upregulated across cancer types and implicated as oncogenes. The function of the studied SNHGs in cancer is ceRNA sponging of miRNAs and direct interaction with mRNA and proteins [45]. We observed 17 significantly expressed transcripts that account for 3.3% of total, significantly expressed lncRNAs (Supplementary Table S4).…”
Section: Cancer-related Snhg Family Members Are Differentially Expres...mentioning
confidence: 93%
“…Many of these lncRNAs are upregulated across cancer types and implicated as oncogenes. The function of the studied SNHGs in cancer is ceRNA sponging of miRNAs and direct interaction with mRNA and proteins [45]. We observed 17 significantly expressed transcripts that account for 3.3% of total, significantly expressed lncRNAs (Supplementary Table S4).…”
Section: Cancer-related Snhg Family Members Are Differentially Expres...mentioning
confidence: 93%
“…Previous research has shown that HOTAIRM1 interacts directly with EZH2 and inhibits the PRC2 complex from binding and depositing H3K27me3 to induce HOXA1 oncogene overexpression. Interestingly, HOTAIRM1 overexpression has been associated with an enhancer situated 150 kb downstream of HOXA1 [ 137 ], and previous research has identified HOTAIRM1 as a major regulator of proliferation, migration, invasion, and epithelial—mesenchymal transition (EMT) in vitro [ 135 , 138 ].…”
Section: Enhancer-lncrnas Interactions In Gynecological Cancersmentioning
confidence: 99%
“…LncRNA encoding genes are widely distributed in introns or exons of mRNA encoding genes ( Lu et al, 2021 ). Most lncRNAs lack the capacity to be translated into proteins, but they could regulate gene expression through various mechanisms ( Yang et al, 2022 ). Indeed, lncRNAs play an important role in presenting relevant tumor prognosis ( Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%